2004
DOI: 10.1348/1359107042304542
|View full text |Cite
|
Sign up to set email alerts
|

Social support, anxiety and depression after chemotherapy for ovarian cancer: A prospective study

Abstract: These data show for the first time that social support and intrusive thoughts, rather than physical parameters, are the principal determinants of psychological morbidity in patients with ovarian cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

21
111
3
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 158 publications
(145 citation statements)
references
References 44 publications
21
111
3
5
Order By: Relevance
“…Worse performance status was associated with increased levels of psychological distress in one good study [15] and one poor study [5], although one average study [21] found no relationship between Karnofsky performance status and levels of depression/anxiety. This suggests inconclusive evidence for a relationship between Karnofsky performance status and levels of psychological distress.…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…Worse performance status was associated with increased levels of psychological distress in one good study [15] and one poor study [5], although one average study [21] found no relationship between Karnofsky performance status and levels of depression/anxiety. This suggests inconclusive evidence for a relationship between Karnofsky performance status and levels of psychological distress.…”
Section: Resultsmentioning
confidence: 88%
“…Levels of depression in ovarian cancer groups tended to be higher than in community samples, with percentages of those scoring above the clinical cut-off ranging from 21-25% in the good studies to 33% in the poor study [5] (though, interestingly, this study found that 23% of individuals experienced little or no distress). Notably, the prevalence of depression decreased after the 3-month period following completion of treatment [21], although it does not appear to differ across the first 6 weeks post-diagnosis [27]. However, it is important to note that studies involving patients who were at varying stages of their cancer journey found that approximately 25% of participants scored above the clinical cut-off, suggesting that depressive symptoms may remain a significant problem for some patients.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations